Pengaruh Pelatihan Dan Pengembangan Sumber Daya Manusia Terhadap Kinerja Karyawan Pada PT. Bumdesma Kusuma Jaya Kecamatan Poncokusumo Kabupaten Malang - Moh. Nur Yahya; Budi Wahono; Arini Fitria Mustapita (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
Abstract In the modern era, global competition such as the industrial revolution 4.0 and MEA (Asian Economic Community) can lead to competition in the world of economy, one of which is in the world of work. In the modern era, global competition such as the industrial revolution 4.0 and MEA (Asian Economic Community) can lead to competition in the world of economy, one of which is in the world of work. In the modern era, global competition such as the industrial revolution 4.0 and MEA (Asian Economic Community) can lead to competition in the world of economy, one of which is in the world of work. Training and development is a form of effort carried out by the organization to increase the ability of its employees. So this study aims to determine the effect of training and human resource development on employee performance from August - September 2021. This research is a quantitative research and is a type of explanatory research. The results of this study indicate that HR training and development has an effect on employee performance, training has an effect on employee performance, and HR development has an effect on employee performance. Keywords: Training, Human Resource Development, and Employee Performance